PENGARUH CORPORATE COVERNANCE, FINANCIAL RATIO DAN CASH FLOW TERHADAP FINANCIAL DISTRESS: Studi Empiris pada Perusahaan Transportasi yang Terdaftar di BEI Tahun 2020-2022 - Ismiyati; Indarto, Bambang Ahmad (Jurnal Ekonomi, Manajemen dan Akuntansi (JEMA) Universitas Ngudi Waluyo, 2024)
Background:Decline Economic activity occurred in the transportation sector due to the Covid-19 pandemic. Transportation companies experienced a sharp decline in profits, leaving the company in a state of disrepair financial distress (Financial distress). The aim of this research is to determine the influence of corporate governance, financial ratio, and cash flow on conditions of financial distress that happened to transportation companies registered on the IDX 2020-2022. Method:This type of research is quantitative using secondary data. The total population is 36 transportation companies registered on the IDX. The sampling technique used purposive sampling and 10 companies were obtained from financial distress. The research instrument uses the SPSS program to process company financial report data. The data analysis method used was descriptive statistical analysis and multiple linear regression. Results:The results obtained by the significance value for the variables board of directors (0.519), board of commissioners (0.144), ROA (0.743), and operating cash flow (0.611) are greater than the probability value of 0.05 so that these variables have no influence on financial distress. Meanwhile, the coefficient value of the variable current ratio value is -22.74 and a significance value of 0.011 (<0.05) is obtained, which means it is variable current ratio negative and has a significant effect on financial distress. Conclusion:Variables that influence financial distress is current ratio.